Task and crisis analysis during surgical training - Wucherer, Patrick; Stefan, Philipp; Weidert, Simon; Fallavollita, Pascal; Navab, Nassir (International Journal of Computer Assisted Radiology and Surgery, 2014)
Purpose: To design a surgical training environment based on task and crisis analysis of the surgical workflow.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Contextual training environment; Haptics; Medical simulation; Surgical training; Team training; VR procedural simulator